1959
DOI: 10.1084/jem.110.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Survival of Staphylococci

Abstract: These studies on the intracellular survival of staphylococci were begun with the idea of investigating possible mechanisms of "cellular immunity" in staphylococcal infections. At that time the reports of Rogers and Tompsett (1) and Baker (2) had stated that virulent staphylococci would not only survive, but actually multiply within human and rat leucocytes. These reports prompted the present authors to see whether staphylococci could multiply within rabbit leucocytes and if this were the case whether rabbits "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

1962
1962
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 7 publications
3
53
0
Order By: Relevance
“…In a previous study (Kapral & Shayegani, 1959) it was reported that Staphylococcus a u r w could survive for several hours within rabbit mononuclear leucocytes. No multiplication or destruction of staphylococci was observed during this interval with the methods used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (Kapral & Shayegani, 1959) it was reported that Staphylococcus a u r w could survive for several hours within rabbit mononuclear leucocytes. No multiplication or destruction of staphylococci was observed during this interval with the methods used.…”
Section: Introductionmentioning
confidence: 99%
“…This tissue-culture procedure was the same as previously described (Kapral & Shayegani, 1959) with the exception that 0.2 ml. of 10% sodium bicarbonate solution was incorporated into the tissue-culture medium and the chambers placed under 5 % CO, to stabilize the pH at 7.4 during the long incubation period, Fifty pg.…”
Section: Introductionmentioning
confidence: 99%
“…S . aureus strain 18-Z; the characteristics of this strain were described previously (Kapral & Shayegani, 1959). From this strain two mutants were derived : (i) 18-Z, ad--an adenine-requiring mutant, which grew slowly without added adenine, and had a lag phase of about 7-10 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Monocytes and polymorphonuclear leucocytes were obtained from rabbits as described previously (Kapral & Shayegani, 1959 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation